PENGARUH CELEBRITY ENDORSERS DAN PESAN IKLAN DI TELEVISI TERHADAP KEPUTUSAN PEMBELIAN PADA ES KRIM WALLS MAGNUM BELGIUM CHOCOLATE - Mariyanti, Luh Dwi; Rahanatha, Gede Bayu (E-Jurnal Manajemen, 2015)
This study aims to determine the effect of Celebrity endorsers and advertising messages on television on purchasing decisions on Magnum ice cream Walls Belgium Chocolate. This research was conducted in the city of Denpasar. The population in this study is that consumers who have been consuming ice cream products walls magnum Belgium Chocolate. Sampling of this research is purporsive sampling technique. Data were collected using a questionnaire. Respondents from the study of 100 respondents. Data analysis techniques used in this research is multiple linear regression analysis. These results indicate that (1) Variable Celebrity endorser positive and significant impact on purchasing decisions partially Walls ice cream Magnum Belgium Chocolate. (2) Variable Message television advertising in a positive and significant influence on purchasing decisions partially Walls ice cream Magnum Belgium Chocolate.
Keywords: celebrity endorsers, pesan iklan di televisi dan keputusan pembelian.